Occurrence of Ochratoxin a and Total Aflatoxins in Capsicum-Derived Spices: A Comparative Estimation Across Countries - Chavez-Rosales, R (Taylor and Francis Ltd., 2025)
The occurrence and distribution of ochratoxin A (OTA) and total aflatoxins (AFs) in capsicum-derived spices (merkén and paprika) commercialised in Chile were analysed and compared using HPLC-FLD. The results highlight a high detection frequency of OTA and AFs, with merkén emerging as the most contaminated spice compared to paprika. Contamination with OTA (84%) was more prevalent than AFs (6%) in both spices. The highest OTA levels in spices were observed in Chile (447.9 ng g−1), China (148.1 ng g−1), Spain (74.4 ng g−1g), and Brazil (74.1 ng g−1). Among the countries analysed, the number of samples exceeding international regulatory limits was highest in Chile and China (n = 10), and the United States (n = 4). The statistical analysis revealed no significant differences in exceedance rates between countries (p = 0.681). Interestingly, the co-occurrence of OTA and AFs was observed in paprika (n = 7; United States = 4, Pakistan = 2; China = 1) and merkén (n = 4; VI (n = 2) and IX region (n = 2), respectively. The EDI and HQ calculations for merkén indicate a higher health risk for consumers compared to paprika. The results of this study underscore the critical need to establish mycotoxin monitoring programs for matrices like spices, which are highly susceptible to contamination by one or more mycotoxins. © 2025 Taylor & Francis Group, LLC.